Abiotic stress and self-destruction: ZmATG8 and ZmATG12 gene transcription and osmotic stress responses in maize. (2019) - Tejeda, Luis Herminio Chairez; Viana, Vívian Ebeling; Maltzahn, Latóia Eduarda; Busanello, Carlos; Barros, Lilian Moreira; da Maia, Luciano Carlos; Costa de Oliveira, Antonio; Pegoraro, Camila
Abstract: Water deficit is one of the most important stresses affecting the maize crop. Whilst the development of osmotic stress tolerant maize ( Zea mays L.) genotypes is an effective approach for reducing yield losses, understanding of the basic mechanisms of response and tolerance is limited. Under normal conditions, autophagy works at baseline levels to maintain cellular homeostasis. However, under abiotic stress conditions, this process intensifies to remove damaged or unwanted cytoplasmic materials or to recycle materials to provide anabolic substrates and metabolites to cells. This process is mediated by ATG genes (AuTophaGy-related genes). Autophagosome expansion and maturation is mediated by ATG8 and ATG12 ubiquitin-like conjugation systems. In this sense, the aim of this study was to characterize the regulation and transcriptional profile of the ZmATG8 gene and isoforms, together with the ZmATG12 gene, in maize landrace seedlings under osmotic stress conditions. A difference in transcript profile was observed between two studied landraces, with higher transcript accumulation in landrace Argentino Amarelo, which was more affected by osmotic stress. Under the stress conditions, all ZmATG genes studied showed an increase in transcript accumulation in shoot tissues in this landrace. In contrast, for landrace Taquarão a reduction in gene expression was detected, with the exception of ZmATG8b . For root tissues under stress, landrace Argentino Amarelo showed an increase in transcript accumulation for the ZmATG genes, with the exception of ZmATG8b, whilst for landrace Taquarão an increase in expression of ZmATG8e and ZmATG12 was observed, with a reduced expression of ZmATG8c . The ZmATG genes presented cis -regulatory elements involved in osmotic stress response via abscisic acid (ABA)-dependent and ABA-independent signaling. As such, it is suggested that the known transcription factors involved in the osmotic stress signaling response may act in the regulation of ZmATG genes. This work provides evidence of autophagy transcriptional signaling in response to osmotic stress in maize.